1998
DOI: 10.1002/(sici)1097-4601(1998)30:7<457::aid-kin1>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Gas-phase kinetics of elimination reactions of pentane-2,4-dione derivatives. Part ii [1]. Thermolysis of derivatives and analogues of 3-phenylhydrazonopentane-2,4-dione

Abstract: Six analogues and derivatives (1-6) of 3-phenylhydrazonopentane-2,4-dione (7) were subjected to gas-phase thermolysis. The Arrhenius log A and Ea (kJ ) of the Ϫ1 Ϫ1(s ) mol analogues (1-5) are, respectively: 10.42 and 140.8 for 1-cyano-1-phenyl-hydrazonopropanone (1), 11.19 and 135.4 for 1-cyano-1-(p-nitrophenylhydrazono)-propanone (2), 10.68 and 144.9 for 1-cyano-1-(p-methoxyphenylhydrazono)propanone (3), 11.76 and 137.8 for 1-cyano-3-phenyl-1-phenylhydrazonopropanone (4), and 11.29 and 145.9 for 1-cyano-1-ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The experimental work reported by Al-Awadi et al 2 suggested that the thermal elimination of oximes passes through a six-membered ring transition state irrespective of substituents and presented the reaction rate coefficients k and Arrhenius activation energies Ea for a series of sulphonyl oximes (Y = OCH 3 , CH 3 , H, and Cl). Discussions about the structures of stationary points on the potential energy surface, energetics, and nature of reaction mechanism in this study will be given for these compounds for the purpose of comparison.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The experimental work reported by Al-Awadi et al 2 suggested that the thermal elimination of oximes passes through a six-membered ring transition state irrespective of substituents and presented the reaction rate coefficients k and Arrhenius activation energies Ea for a series of sulphonyl oximes (Y = OCH 3 , CH 3 , H, and Cl). Discussions about the structures of stationary points on the potential energy surface, energetics, and nature of reaction mechanism in this study will be given for these compounds for the purpose of comparison.…”
Section: Resultsmentioning
confidence: 99%
“…Polar substituent effects are investigated extensively in kinetic investigations of reaction mechanism. In this work, several substituents Y=OCH 3 , CH 3 , H, Cl, NO 2 , are chosen at the para position in the Yphenyl rings. We take a series of oximes as an example to study the effect of the substituents of Y-ring on the reactivity and properties of molecules.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In these studies the proposed mechanisms were concerted asynchronous processes involving a cyclic six‐membered TS (Scheme ), and molecular reactivities were reported to be a function of the H‐bond donor acidity of the HX bond (i), the polarity of the AB bond (ii), the protophilicity of the YZ multiple bond (iii), or an effect combining two or all of the three bonds (Scheme ). Reactivity might additionally be subject to the thermodynamic stability of the incipient elimination fragments 8,16.…”
Section: Introductionmentioning
confidence: 99%